Genetic variability and character association among maize (Zea mays L.) Inbred lines (Bangladesh Journal of Botany, 2024)
Genetic analysis of variability, heritability and character association was studied among 25 maize inbred lines for eleven traits. The ANOVA indicated significant variation existed among the inbred lines chosen for the study for all the traits. Wide range of variability was observed for all the traits among them grain yield varied from 16.03 to 62.52 q/ha with an average mean value of 45.75 q/ha. Phenotypic variance was higher compared to genotypic variance and highest phenotypic variance was observed for plant height followed by grain yield. However, the difference between phenotypic and genotypic variance was very narrow for majority of the traits. Similarly, phenotypic coefficient of variation (PCV) was marginally higher than genotypic coefficient of variation (GCV) and highest GCV and PCV was recorded for grain yield (37.03, 38.12) followed by ear height (24.12, 26.48) indicating that these characters are under genetic control have high potential for selection. The high amount of broad-sense heritability coupled with high genetic advance as a percent mean (GAM) was observed for grain yield (0.94 and 74.12) followed by number of kernels per row (0.90 and 32.88) indicating phenotypic based selection for these traits would be successful. Hundred grain weight had the highest genotypic correlation (0.834) with grain yield followed by number of kernels per row (0.623).Bangladesh J. Bot. 53(1): 57-65, 2024 (March)